Desenvolvimento territorial: a experiência do Território do Sisal na Bahia - Silva, Filipe Prado Macedo da (2012)
The goal of this work is to study the Territory of Sisal. Located in the semiarid region of Bahia, the Territory of Sisal covers 20 counties: Araci, Barrocas, Biritinga, Candeal, Cansanção, Conceição do Coité, Ichu, Itiúba, Lamarão, Monte Santo, Queimadas, Retirolândia, São Domingos, Quijingue, Nordestina, Santaluz, Serrinha, Teofilândia, Tucano, and Valente. In the Territory of Sisal, since 1960, civil society has been organized and the government has put into operation several successful projects. The Territory of Sisal was formed from the recent implementation of territorial development policies. However, 10 years after the adoption of the territorial approach, the Territory of Sisal continues to experience low economic progress and high levels of poverty and social exclusion. Why it is that, despite the strong presence of social actors and local institutions (civil society) and its designation as a territory of public policy, the Territory of Sisal continues to register some of the worst social and economic statistics in Bahia and Brazil? To answer this question, this work aims at exploring how civil society in the Territory of Sisal was organized and how it was able to establish collective enterprises and understand why, despite this the territory continues to display some of the worst socioeconomic indicators in Bahia and Brazil. Using primary data and secondary data beyond the perspective of neocorporativism and the territorial approach this work has revealed that the Territory of Sisal, in Bahia, still has much to do to achieve a high level of socioeconomic development, especially because it must overcome some obstacles, such as economic dependence on municipal governments, the \"natural phenomenon of drought,\" the decay of the sisal production chain, the dichotomy between urban (city) and rural (countryside) interests, and excessive conflicts, both \"open\" and \"closed,\" that hinder the development of social cohesion.